Lipid Metabolism - Valenzuela Baez, Rodrigo (IntechOpen, 2013)
Lipids (fats and oils) are a wide range of organic molecules that serve several functions in organisms. Lipids are essential components of our diet, highlighting their important contribution in energy, representing 9 kcal/g (or 37.7 kJ/g), and by some components relevant to the metabolism, such as essential fatty acids, fat soluble vitamins and sterols (cholesterol and phytosterols). Besides this, lipids have key roles in human growth and development, along with promoting, preventing and/or participating in the origin or eventually in the treatment of various diseases. This book presents a systematic and comprehensive review about the structure and metabolism of lipids, particularly highlighting the importance of these molecules in the body and considering the interest of some lipids in health and disease.